Furan-based polyesters from renewable resources: Crystallization and thermal degradation behavior of poly(hexamethylene 2, 5-furan-dicarboxylate). (June 2015) - Papageorgiou, George Z.; Tsanaktsis, Vasilios; Papageorgiou, Dimitrios G.; Chrissafis, Konstantinos; Exarhopoulos, Stylianos; Bikiaris, Dimitrios N.
Graphical abstract: Highlights: PHF can be prepared from monomers derived from renewable resources. PHF has a high crystallization rate. The equilibrium melting point of PHF was found 157 °C. The heat of fusion for the pure crystalline PHF was estimated to be about 143 J/g. The thermal stability of PHF is very high. Abstract: In the present study poly(hexamethylene 2, 5-furan dicarboxylate) (PHF), a polyester prepared from monomers derived from renewable resources, was synthesized by applying the melt polycondensation method. The polymer exhibited a melting temperature of about 145 °C while the glass transition temperature was 7 °C. After isothermal crystallization, PHF showed multiple melting behavior which was attributed to partial melting–recrystallization and final melting. The equilibrium melting temperature of the polymer was found to be 157 °C, while the heat of fusion of the purely crystalline material was found to be 34 kJ/mol (143 J/g). A crystallization regime I to regime II transition was observed at 134 °C as a breakpoint in the Lauritzen–Hoffman plot. The Kg I and Kg II values were calculated 0.9 × 10 5 and 1.76 × 10 5 respectively. Polarized optical microscopy was also employed for the study of the isothermal crystallization of PHF. PHF can be regarded thermally stable since its decomposition starts above 350 °C. Thermal degradation kinetics were investigated by means of thermogravimetric analysis.